(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Intranasal delivery of peptides offers a promising alternative to traditional routes of administration, presenting unique advantages in terms of rapid onset of action and avoidance of first-pass metabolism. Despite its potential, the development of intranasal peptide therapies is fraught with significant challenges, including peptide stability, absorption efficiency, and delivery precision. This review delves into the complexities of formulating intranasal peptide therapeutics, highlighting the pivotal role of advanced formulation technologies and innovative delivery devices. Key strategies to enhance peptide stability involve the use of protective carriers and chemical modification. Improving absorption efficiency relies on the development of permeation enhancers and mucoadhesive formulations, tailored to the unique anatomy and physiology of the nasal cavity. Furthermore, an in-depth understanding of nasal physiology is essential for optimizing drug delivery and maximizing therapeutic outcomes. Recent advancements in nanoparticle-based systems and microfabricated delivery devices are also discussed as cutting-edge approaches to overcome these hurdles. As research continues to evolve, the integration of these technological innovations with a robust understanding of nasal drug delivery mechanisms holds the key to unlocking the full potential of intranasal peptide therapies.